Roles of extension agents towards agricultural practice in Malaysia - Arif Shah, Jasmin; Asmuni, Azizan; Ismail, Azahari (Indonesian Society for Knowledge and Human Development, 2013)
It is expected that the income generated by paddy industry will increase up to 988 million per year. In order to achieve this, extension agents plays important role in educating farmers by encouraging them to learn, adopt new technologies and spread them to other farmers. To ensure the success of extension program, the agents should recognize their roles as change agents (as a catalyst, solution giver, process helper, and resource linker) and have ability to acquire competencies to accomplish these roles. Thus, this study aims to explore the level of roles among extension agents. Using a quantitative survey methodology, self-administered questionnaires measuring the roles of extension agents as change agents. A total of 117 extension agents had participated in this study. The extension agents were the officers from various agricultural departments and agencies who serve paddy farmers in Malaysia region in related to extension, marketing, financing, farmers association, production, and others. The finding showed that the level of roles among extension agents is high. Hence, the competency of extension agents in Malaysia is indeed especially as a change agents and one of the important determinants of success for agriculture industry in Malaysia. This study emphasized that in order to improve the performance of agricultural extension agents, one of the way is by getting to know their competencies, skills and abilities. The extension agents, Farmers, policy makers, researchers, academics and people working in agriculture can learn a great deal about what individuals and institutions need to do to develop farmers, personally and professionally.